PHYSICOCHEMICAL PARAMETERS OF MAGMATIC AND HYDROTHERMAL PROCESSES AT THE YAMAN-KASY MASSIVE SULFIDE DEPOSIT, THE SOUTHERN URALS - Simonov V.A.; Kovyazin S.V.; Terenya E.O.; Maslennikov V.V.; Zaykov V.V.; Maslennikova S.P. (My University, 2006)
Melt and fluid inclusions in minerals have been studied and physicochemical parameters of magmatic processes and hydrothermal systems estimated at the Yaman-Kasy copper massive sulfide deposit in the southern Urals. It was established that relatively low-temperature (910-945°C) rhyodacitic melts belonging to the tholeiitic series and containing 2.7-5.2 wt % water participated in the formation of the igneous complexes that host the Yaman-Kasy deposit. As follows from ion microprobe results, these silicic magmas had a primitive character. In the distribution of trace elements, including REE, the rhyodacites are closer to basaltic rather than silicic volcanic rocks, and they are distinguished in this respect from the igneous rocks from other massive sulfide deposits of the Urals and the Rudny Altai. Two types of solutions actively took part in the formation of hydrothermal systems: (1) solutions with a moderate salinity (5-10 wt % dissolved salts) and (2) solutions with a low salinity (a value close to that of seawater or even lower). Concentrated fluids with more than 11.5 wt % dissolved salts were much less abundant. Hydrothermal solutions heated to 130-160, 160-270, or occasionally 280-310°C predominated in ore formation. The sequence of mineral-forming processes at the Yaman-Kasy deposit is demonstrated. Mineral assemblages were formed with an inversion of the parameters characterizing ore-forming solutions. An increase in the temperature and salinity of solutions at the early stages was followed by a decrease at the final stages. The evolution of the hydrothermal system at the Yaman-Kasy deposit has much in common with the parameters of black smokers in the present-day Pacific backarc basins. © Pleiades Publishing, Inc. 2006.